“Eu nasci para ser assistente social”: o trabalho em serviço social, profissionalização, identidade e gênero - Bolzan, Débora de Paula (2014)
This dissertation aims to analyze sociologically labor relations in social work in the metropolitan area of Goiânia, revealing how the social workers are affected and experience the changes taking place in the universe of work and its implications for the category. Still, there are as specific objectives: to outline the socioeconomic profile of social workers; to analyze the process of construction of social identities of these professionals; and to identify how ownership of emotional labor and gender constructions affect the profession. The methodology has qualitative emphasis. A semistructured interview with social workers was the main procedure for the construction of qualitative data, with technical elements of narrative interviews. The quantitative data were used as sources of secondary data bases, as Census, PNAD and RAIS sources. The results indicate a visible process of casualization of working conditions in social service, particularly with respect to the type of job contract (temporary contracts, commissioned position, volunteer work), diferent types of work journey arrangements, widely disparate wages, unstable links and absence of social rights (holidays, maternity leave, etc). Even workers with effective statutory relationship are affected by the dichotomy of contracts, reduction of competitions for public servants and scarce investment in physical, material and human conditions of work. The results also indicate that the Social Work persists as female niche, which has a historical and social devaluation, exposed mainly in discriminatory manifestations related to career choice of Social Work. Social workers manage their gender relations in the permanence of housework reconciled to professional work, setting up a gender identity. Finally, the research exposes that emotional labor is done intermittently in this profession and that emotions are administered in depth level, contributing to the emotional labor be constituted as part of the professional identity.